Соціально-правові та морально-етичні проблеми застосування штучного інтелекту та інформаційно-комунікаційних технологій - Філіпенко, Н. Є.; Filipenko, N. Ye.; Лукашевич, С. Ю.; Lukashevych, S. Yu.; Андреєва, О. О.; Andreieva, O. O.; Салаєва, К. А.; Salaieva, K. A.; Салаєва Карина Анатоліївна (Вісник Пенітенціарної асоціації України. - 2023. - № 4(26). - С. 95-103, 2023)
В статті розкрито сутність соціальних та етичних вимог до застосування інформаційно-комунікаційних технологій і штучного інтелекту в житті сучасної людини, соціуму й держави. Наголошено, що наявне етичне регулювання їх застосування здебільшого обмежено рамковими, декларативними документами, які позначають лише загальні підходи та мету взаємодії людства із системами штучного інтелекту. Акцентовано, що використання штучного інтелекту потребує спеціального правового регулювання, оскільки йдеться про життя та здоров’я людей. Через потенційну небезпеку для цивілізації інформаційно-комунікаційних технологій і штучного інтелекту необхідно суворо ліцензувати діяльність, пов’язану з виробництвом і експлуатацією таких систем.

Article reveals the essence of social and ethical requirements for the use of information-communication technologies, and Artificial Intelligence in the life of modern individuals, society, and the state is revealed. The analysis of professional literature and normative legal acts, both domestic and foreign, allowed identifying a specific feature of Artificial Intelligence, which is the uniqueness of the source base for Artificial Intelligence use research, in our opinion. In addition to scientific and philosophical works, it must be considered the regulatory documents containing information about the current challenges faced by individuals in the practical use of artificial intelligence systems in various spheres of society, as well as legal norms, moral principles regulating Artificial Intelligence, rules, and requirements already formulated by various social institutions and organizations in response to the challenges of the new digital reality. The authors conclude that ethical regulation of the information-communication technologies, and artificial intelligence use generally comes down to the adoption of framework, declarative documents that outline only general approaches and goals of the interaction between society, its individual social and professional groups, and Artificial Intelligence systems. Ethical principles of the development, implementation, and evolution of artificial intelligence systems, contained in these documents, typically play a role as a kind of warning humanity against potential negative consequences of technology use. However, despite a considerable overlap in the proposed principles, the content of these norms remains largely undisclosed. All the aforementioned confirms the importance and significance of the chosen research goal and indicates the necessity of a social and ethical comprehension of the most current issues in the use of artificial intelligence capabilities.

В статье раскрыта сущность социальных и этических требований к применению информационно-коммуникационных технологий и искусственного интеллекта в жизни современного человека, социума и государства. Отмечено, что существующее нравственное регулирование их применения в основном ограничено рамочными, декларативными документами, обозначающими только общие подходы и цель взаимодействия человечества с системами искусственного интеллекта. Акцентировано, что использование искусственного интеллекта требует специального правового регулирования, поскольку речь идет о жизни и здоровье людей. Из-за потенциальной опасности для цивилизации информационно-коммуникационных технологий и искусственного интеллекта необходимо строго лицензировать деятельность, связанную с производством и эксплуатацией таких систем.
Socio-legal, moral and ethical issues of artificial intelligence and information and communication technologies
Keywords: штучний інтелект; інформаційні технології; інформаційно-комунікаційні технології; соціальні проблеми; моральні та етичні проблеми; правове регулювання; artificial intelligence; information technology; information and communication technologies; social issues; moral and ethical issues; legal regulation; искусственный интеллект; информационные технологии; информационно-коммуникационные технологии; социальные проблемы; моральные и этические проблемы; правовое регулирование